Pengaruh IESQ (Intelektual, Emosional And Spiritual Quotient) Terhadap Komitmen Organisasional Pada CV. Mitra Widyatama Probolinggo - Judi Suharsono; Yuda Ria Pratama (Ecobuss, 2018)
The Aim of this research are: 1) To investigate the influence IESQ (Intellectual, Emotional and Spiritual Quotient) simultaneously and partially on Organizational Commitment on the CV. MitraWidyatama Probolinggo. Writing of this, researchers used quantitative research analysis with the causal associative approach and take a sample of 78 respondents, the data collection methods using questionnaires and sampling techniques using saturated sampling. Results of the study show the whole item Test Validiitas valid question that is above 0.223 and the results showed a Test Reliability Reliable is above 0.60. Partial Test Intellectual Quotient (X1) to demonstrate organizational commitment is partially affected by Value tcount> t table (4.452> 1.992) (sig. 0.028 <0.05). Emotional Quotient Test (X2) to demonstrate organizational commitment is partially affected by a count value ≥ table (7.096 ≥ 1.992) (sig. 0.000 ≤ 0.05). And Spiritual Quotient Test (X3) on organizational commitment showed partial effect Rated hitung ≥ table (5.352 ≥ 1.992) (sig. 0.028 ≤ 0.05). Correlation Analysis of Multiple Retrieved number R of 0.736, indicating that there is a very strong relationship. Determination Analysis Retrieved number R2 (R Square) of 0.541, indicating that the percentage contribution of the influence of the independent variable on the dependent variable of 54.1%. This study supports the results of research conducted by Zakiah (2013), Ervita (2016) and Tobias (2017). Keywords: Intellectual Quotient, Emotional Quotient, Spiritual Quotient and Organizational Commitment.